Optimization Of The Performance Of The Marriage Advisory, Guidance, Preservation Agency (BP4) In Relation To The Divorce Rate In The Bandung High Religious Court (PTA) Area - Koidin; Aen, I Nurol; Rasyid, Fauzan Ali; Anwar, Syahrul; Ridwan, Ahmad Hasan (Program Studi Hukum Keluarga Islam, 2024)
This research starts from the fact that shows the high divorce rate in Indonesia, this is evidence of the absence of household harmony that is not sufficient before entering into marriage, so the State is responsible as ordered by law, for the welfare of its people, making their households happy and eternal, that is where the State must be present and act to realize the households of its people happy and prosperous, one of which is by establishing premarital education early on as a concrete step to reduce the high divorce rate in Indonesia. The purpose of this study is to determine and analyze the optimal function of BP4 in tackling the divorce rate, the divorce rate in the PTA Bandung area 2017 to 2022, the function of BP4 in relation to the competence of judges, and BP4's efforts to reduce the divorce rate in the PTA Bandung area. The results of this study indicate that, First, Optimizing the Function of the Marriage Counseling, Guidance, Preservation Agency in relation to the high divorce rate in the Bandung PTA area, including: enhancing and improving the quality of marriage and happy families, preventing underage marriage, preventing unhealthy polygamy, and providing information advice in guidance to those concerned about Nikah, Talak and Rujuk (NTR) issues, especially for broken home households.